Adoption of safer sex practices among male youngsters - an abstract - Ednaldo Cavalcante de Araújo (Online Brazilian Journal of Nursing, 2006)
The present study of a qualitative research nature was based on concepts included into the Social Representation Theory as developed by Serge Moscovici et al., (1978) and carried out within a Fundamental and Intermediate level State School located in the city of João Pessoa, Paraíba, Brazil. It was intended to survey and carefully examine the difficult questions concerning the adhesion of male youngsters to safe sex practices, and at the same time, search for adequate subsidies to understand, modify, and/or supplement the nature of informations related to HIV and AIDS. Those informations are imbricated into the perceived and culturally constructed facts through gender relationships, thus emphasizing the psychosocial view in this area of investigation. The adoption of a theoretical–methodological referent to guide this study capacitated the investigation to organize the concepts’ sets which compose a given theory and also capture with highest accuracy, the essence of the phenomenon under study. Choosing this theory concepts to serve either as a referent and an investigative and expositive method in this study, is then justified not only for complexity or the problem to be investigated but also because it is compatible with the investigators’ world view. A semi-structured interview based on the present study’s propose was the technique used in order with 21 male youngsters from October 1997 to June 1998; the interviews were previously ascertained according to each the subjects’ availability. Results were attained by the use or part of the Content Analysis (Bardin, 1997) technique viewing that this technique may be applied to any communication with the transference of meanings from an issuing agent to a receiver an also because it makes use of systematic procedures to describes the messages’ content and thus able to extract from them the indicators which allow to infer the knowledge related to the these messages’ production condition, known as one of she Social Representation theory goals two categories could be defined: 1) Understandig the safer sex practices; 2) Understanding HIV and AIDS. Results showed the diversity of meaning and an harmonization tendency concerning the youngsters‘ understanding of safe sex practices, HIV and AIDS while their discourses showed peculiar characteristics and conjured similar meanings converging to some central points of the analysis which expressed the social representation of the investigated themes enabling the elaboration of educational proposal.